Improving Livelihoods of Smallholder Coffee Communities in Papua New Guinea. - Curry, George; Sharp, Timothy; Kiup, E.; Thomas, M.; Tilden, G.; Aroga, L.; Koczberski, G.; Hamago, M.; Togonave, P. (ACIAR, 2024)
Smallholder farmers in Papua New Guinea (PNG) face significant challenges, including labour shortages, low returns on labour, poor post-harvest processing, land pressures, and the recent threat of Coffee Berry Borer (CBB), a pest endangering the coffee industry. To address these issues, a research project was conducted, focusing on three components: a farmer training package, a demucilager (mini wet mill) trial, and intercropping coffee with food crops. The research involved extensive fieldwork using both quantitative and qualitative methods. The farmer training package consisted of 25 modules developed collaboratively with extension officers, smallholders, industry personnel, and researchers. It adopted a holistic ‘whole of farm’ approach, recognising the diverse livelihoods and socio-cultural activities of smallholders. A key module focused on CBB management, developed in partnership with HORT/2018/194, is now widely used. The overall package aims to strengthen links between farmers, exporters, and processors, ensuring the long-term sustainability of PNG’s coffee industry.